IDDF2018-ABS-0175 Functional lumen imaging probe assessment of anal canal distensibility. (June 2018) - Chen, Ssu Chi; Futaba, Kaori; Leung, Wing Wa; Wong, Cherry; Mak, Tony; Ng, Simon; Gregersen, Hans
Abstract : Background: The mechanism of defaecation and continence is a complex process involving several factors. Identifying the cause of faecal incontinence is often difficult. Assessment of patients currently involve functional assessment with high-resolution anorectal manometry (HR-ARM) and anatomical assessment using Endoanal ultrasound (EAUS) scan, providing limited information. EndoFLIP (Functional Lumen Imaging Probe) allows additional assessment of anal canal distensibility. 1 2 Aim: To compare anal canal function using EndoFLIP between faecally incontinent patients (FI) and asymptomatic subjects (AS). Methods: All subjects were assessed using HR-ARM, EAUS and EndoFLIP. Using the EndoFLIP, continuous ramp distension was carried out up to 5=bag vol. In second ramp distension, the 5=volume was maintained while the subjects were asked to squeeze their anus. Anal competence of the narrowest area of the anal canal was evaluated using three distinct parameters derived from the EndoFLIP data. Mann-Whitney's U test was used for statistical analysis. Results: Sixteen FI patients (2M/14F, Mean age 61.38 years, SEM +3.34) and 9 AS (3M/6F, Mean age 57.9 years, SEM +3.69) were assessed. The median yield pressure (the pressure when the diameter increased from baseline) was significantly lower in the FI group at 22.99 cmH2 0 (17.67–45.49 cmH2 0) compared to 55.95 cmH2 0 (36.56–64.82 cmH2 0) in asymptomatic subjects. There was no significant difference in the distensibility between the FI group 0.18 (0.17–0.35) mm/cmH2 0 compared to AS group 0.23 (0.12–0.39) mm/cmH2 0 calculated as the change in diameter divided by the change in distension pressure. The squeeze strength was significantly higher in the AS group 167.3 (62.0–270.8) mm.cmH2 0 compared to FI group 23.6 (8.1–86.1) mm.cmH2 0. Conclusions: EndoFLIP demonstrated that FI patient's anal sphincters yielded at a lower pressure and had lower squeeze strength than in asymptomatic subjects, which may be clinically more relevant than squeeze pressures alone.